An analysis of the contents of EDPITAF social studies II teaching guide (1975 final revision) - Tapere, Faustino C. 1926- (1979)
This study aimed to analyze the contents of the EDPITAF Social Studies II Teaching Guide for the second year high school. The teaching guide is divided into six teaching units with every unit assigned to a particular concept as follows: Environment, Social Organization, Change, Interdependence, National Heritage, and An Introduction Unit on the Philippine Constitution of 1973. It has five parts namely, notes to the teacher, objectives, content, process or lesson proper, and evaluation. The contents of the guide aim to develop values and social skills in the young learner, in the hope that he may become a useful and worthy member of society. All the implications derived from the contents of the teaching guide per teaching unit appeared to be relevant to the national development goals.
"May, 1979."
Vita.
Lacking leaves 1-2.
Thesis (M.A.T. Social Studies)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines